2018
DOI: 10.1101/293399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tissue dependent expression of bitter receptorTAS2R38mRNA

Abstract: TAS2R38 is a human bitter receptor gene with a common but inactive allele and people homozygous for the inactive form cannot perceive certain bitter compounds. The frequency of the inactive and active form of this receptor is nearly equal in many human populations and heterozygotes (with one copy of the active form and another copy of the inactive form) have the most common diplotype. However, heterozygotes differ markedly in their perception of bitterness, in part perhaps because of differences in TAS2R38 mRN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…The TAS2R38 expression in SAT and VAT is similar among subjects with the three P49A genotype variants, suggesting that the expression of this bitter receptor in human adipocytes is not influenced by this genetic component. This result agrees with what observed in sino-nasal tissues and tongue papillae where genotype variants of TAS2R38 did not affect the mRNA expression of the receptor [14]. Furthermore, we observed that the in vitro stimulation of the TAS2R38 receptor with a specific agonist (PROP) modulates fundamental processes of adipocyte metabolism, such as delipidation and lipid accumulation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The TAS2R38 expression in SAT and VAT is similar among subjects with the three P49A genotype variants, suggesting that the expression of this bitter receptor in human adipocytes is not influenced by this genetic component. This result agrees with what observed in sino-nasal tissues and tongue papillae where genotype variants of TAS2R38 did not affect the mRNA expression of the receptor [14]. Furthermore, we observed that the in vitro stimulation of the TAS2R38 receptor with a specific agonist (PROP) modulates fundamental processes of adipocyte metabolism, such as delipidation and lipid accumulation.…”
Section: Discussionsupporting
confidence: 92%
“…Over the past decade, it has become evident that taste receptors are expressed not only in taste buds of the tongue surface but also in extra gustatory organs (such as: digestive, respiratory, genitourinary systems, heart, brain, thyroid, skin, placenta and immune cells) suggesting that different cell type, outside the oral cavity, may use taste receptors [13][14][15]. The exact role of TAS2R38 outside the gustatory systems is still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…To understand whether the genes identified by GWAS might be acting at the level of the receptors in taste tissue (as opposed to in the brain or in other tongue tissue, e.g., the filiform papillae), we compared the mRNA expression of these genes to those previously implicated in the peripheral aspects of fat taste perception (e.g., the candidate gene CD36 ) in human taste tissue. To do so, we collected fungiform papillae from subjects recruited for our previous study (Douglas et al 2019) using published procedures (Spielman et al 2010) and isolated the RNA following the manufacturer’s directions, processing the taste tissue with Quick-RNA MiniPrep R1054 (Zymo Research, Irvine, CA). We evaluated RNA quality expressed as an RNA integrity number (RIN) using the Agilent 2200 TapeStation system (Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
“…To understand whether the genes identified by GWAS might be acting at the level of the receptors in taste tissue (as opposed to in the brain or in other tongue tissue, e.g., the filiform papillae), we compared the mRNA expression of these genes to those previously implicated in the peripheral aspects of fat taste perception (e.g., the candidate gene CD36 ) in human taste tissue. To do so, we collected fungiform papillae from subjects recruited for our previous study ( Douglas et al 2019 ) using published procedures ( Spielman et al 2010 ) and isolated the RNA following the manufacturer’s directions, processing the taste tissue with Quick-RNA MiniPrep R1054 (Zymo Research). We evaluated RNA quality expressed as an RNA integrity number (RIN) using the Agilent 2200 TapeStation system (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%